Preparation Methods and Thermal Performance of Hybrid Nanofluids - M. Adamu, Idris; Che Sidik, Nor Azwadi; Jamil, Muhammad Mahmud (Journal of Advanced Research in Applied Mechanics, 2020)
Hybrid nanofluid is a new nanotechnology fluid that is synthesized by dispersing two different nanoparticles into conventional heat transfer fluid. Recently, researchers have indicated that hybrid nanofluids can effectively substitute the convectional coolant especially those working at very high temperatures. In this paper a comprehensive literature on the synthesis of hybrid nanoparticles, hybrid nanofluid and thermal performance of hybrid nanofluid have been compiled and reviewed.